Eleocharis paranapiacabensis and E. raquellyrae: two new and endangered aquatic species of Eleocharis (Cyperaceae) from Brazil - Farias, Diego C.; Alves, Marccus (Phytotaxa, 2026)
Here, two new species of aquatic sedges are described. Both new species belong to Eleocharis ser. Maculosae (Cyperaceae). They are endemic and occur in humid environments within the Atlantic Forest (in São Paulo state, Southeastern Brazil) and Caatinga (in Pernambuco state, Northeastern Brazil) biomes. Diagnostic morphological characters, illustrations, habitat descriptions, distribution maps, and an identification key are provided. Preliminary conservation assessments assert E. paranapiacabensis as Critically Endangered and E. raquellyrae as Endangered, highlighting the need for urgent conservation actions.